Portraying the Aztec Past : the Codices Boturini, Azcatitlan, and Aubin - Rajagopalan, Angela Herren (Recovering languages and literacies of the Americas., 2019)
During the period of Aztec expansion and empire (ca. 1325-1525), scribes of high social standing used a pictographic writing system to paint hundreds of manuscripts detailing myriad aspects of life, including historical, calendric, and religious information. Following the Spanish conquest, native and mestizo tlacuiloque (artist-scribes) of the sixteenth century continued to use pre-Hispanic pictorial writing systems to record information about native culture. Three of these manuscripts-Codex Boturini, Codex Azcatitlan, and Codex Aubin-document the origin and migration of the Mexica people, one of several indigenous groups often collectively referred to as "Aztec."0In Portraying the Aztec Past, Angela Herren Rajagopalan offers a thorough study of these closely linked manuscripts, articulating their narrative and formal connections and examining differences in format, style, and communicative strategies. Through analyses that focus on the materials, stylistic traits, facture, and narrative qualities of the codices, she places these annals in their historical and social contexts. Her work adds to our understanding of the production and function of these manuscripts and explores how Mexica identity is presented and framed after the conquest